Motivational factors influencing post MCO continuous online purchase: A study on Klang valley consumers - Lau, Jia Wen (2022)
The COVID-19 epidemic has presented the world with unprecedented problems and resulted to a new normal way of living. The government of Malaysia has implemented a policy known as the Movement Control Order (MCO), which has resulted in the closure of commercial and industrial establishments as well as government and educational facilities in an effort to reduce the spread of the virus. E-commerce online shopping platforms are seen as a route for the community to meet demands without leaving their homes, which has led to a significant increase in online buying as a result of constraints on freedom of movement. MCO has altered the purchasing habits of consumers. This study aims to evaluate the motivational factor and satisfaction associated with online purchase intention continuation. The Technology Acceptance Model (TAM) and the Expectation Confirmation Model (ECM) were combined to investigate the motivational factors that influence the desire to continue online buying. Klang Valley was surveyed to acquire representative samples of data. Using SPSS and Smart PLS 4.0, empirical data from 301 customers was tested against the suggested model. The results indicate that all hypotheses have a substantial impact on the relationship between satisfaction and intention to continue online purchasing. The perceived ease of use is the most influential motivating factor in this study. Continuance online shopping satisfaction depends heavily on customer satisfaction. This study concludes with recommendations derived from the implications of the findings.